Indigenous Agency in the Amazon : The Mojos in Liberal and Rubber-Boom Bolivia, 1842-1932 - Van Valen, Gary (Book collections on Project MUSE., 2013)
The largest group of indigenous people in the Bolivian Amazon, the Mojos, has coexisted with non-Natives since the late 1600s, when they accepted Jesuit missionaries into their homeland, converted to Catholicism, and adapted their traditional lifestyle to the conventions of mission life. Nearly two hundred years later, they faced two new challenges: liberalism and the rubber boom. White authorities promoted liberalism as a way of modernizing the region and ordered the dismantling of much of the social structure of the missions. The rubber boom created a demand for labor, which took the Mojos away from their savanna towns and into the northern rain forests. The author postulates that as ex-mission Indians who lived on a frontier, the Mojos had an expanded capacity to adapt that helped them meet these challenges. Their frontier life provided them with the space and mindset to move their agricultural plots and cattle herds, join independent indigenous groups, or move to Brazil. Their mission history gave them the experience they needed to participate in the rubber export economy and the politics of white society. The author also argues that the indigenous Mojos also learned how to manipulate liberal discourse to their advantage. This book demonstrates that the Mojos were able to survive the rubber boom, claim the right of equality promised by the liberal state, and preserve important elements of the culture they inherited from the missions.